Practices of sexual education: an analysis in municipal schools in the south of Brazil - Denise Regina Quaresma da Silva; Oscar Ulloa Guerra (Arizona State University, 2011)
This article approaches a characterization of the practices of sexual education in educative institutions in Novo Hamburgo, Rio Grande do Sul, Brazil, where the precocious gestations have a significative extension. We rescued some theoretical contributions to understand the sexual education, specifically from the pos-structuralism, and from current researches about this topic. Besides, we show qualitative results from the interviews with directives and teachers of the fifty six schools of the municipality.